(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Positive growth in palm oil Industry resulting in large quantities of solid waste generation and created a major disposal problem to the country. Among the major solid wastes generated from oil palm manufacturing processed are empty fruit bunches (EFB), mesocarp fruit fibres (MF) and palm kernel shells (PKS). This study investigated the utilization of EFB as sound absorption material for noise control in building. The effect of different form of EFB (coir and dust) was investigated in three different thicknesses (6mm, 12mm and 18mm) to determine the maximum sound absorption coefficient (SAC) and optimum frequencies. All samples were tested using impedance tube at low and high frequencies guided by BS EN ISO 10534. Results shows that dust EFB samples absorbed more sound energy compared to coir EFB samples at both low and high frequency region. Maximum SAC obtained by 18mm thick dust EFB samples at low frequency is 0.6 at 1500Hz while at high frequency; the maximum absorption was also obtained by 18mm thick dust EFB samples with SAC value of 0.990 at 3750Hz.Â This result indicated that thicker samples absorbed more sound energy compared to thinner samples. Moreover, small particles fibers consequently create less pores to the samples with higher density and higher sound absorption. In conclusion, palm oil fibre is highly potential to be used as raw material for sound absorption material replacing synthetic materials since these fiber are renewable, cheaper, nonabrasive, abundance and give less negative effect to human health.